Health effects of androgen abuse: a review of the HAARLEM study. Issue 6 (4th December 2022) - Smit, Diederik L.; Bond, Peter; de Ronde, Willem
Abstract : Purpose of review: Data on the health effects of androgen abuse are mainly derived from lower level evidence, such as case series and cross-sectional studies. In the last few years a relatively large and prospective cohort initiative, the HAARLEM (health risks of anabolic androgenic steroid use by male amateur athletes) study, made an important contribution to current knowledge. Recent findings: The HAARLEM study showed that all androgen abusers experience positive and negative effects, such as an increase in strength and acne and gynecomastia, respectively. Effects are generally reversible and acute life-threatening toxicity is rare. There is a distinct but limited impact on liver and kidney function. Gonadal function is disrupted but resumes normally after abuse is discontinued in the majority of athletes. The negative impact of androgens on cardiovascular parameters, such as blood pressure, hematocrit and lipid metabolism, as well as cardiac structure and function, seems to be the mechanism for premature atherosclerosis and cardiomyopathy, respectively, in long-term users. Summary: It is beyond dispute that androgen abuse is harmful and much of the short-term toxicity is well documented. To prevent the long-term health hazards, there should be ample focus on preventive measures, both primary and secondary, and effective harm reduction strategies should be developed.